AKTIVITAS TABIR SURYA FRAKSI METANOL DARI DAUN SIMPUR (Dillenia indica Linn.) DAN KARAKTERISASI SENYAWA ISOLATNYA - Salatiana Salatiana; Endah Sayekti; Gusrizal Gusrizal (Indonesian Journal of Pure and Applied Chemistry, 2023)
Sunscreen activity has been tested on simpur leaves (Dillenia indica Linn.) by determining the value of sun protection factor (SPF), erythema transmission percentage (%Te) and pigmentation transmission percentage (%Tp) of each methanol extract, n-hexane, dichloromethane fraction, and methanol fraction from simpur leaves. This test was carried out using a UV-Vis spectrophotometer (λ = 200-400 nm), a variation of sample concentration of 50; 75 and 100 ppm. The methanol fraction at a concentration of 100 ppm showed the highest SPF value of 4.630 ± 0.043 and the lowest %Te and %Tp values of 32.316 ± 0.297 and 52.699 ± 0.160, respectively. Isolation of flavonoids from the methanol fraction produced a relatively pure isolate (Rf = 0.901) with code G1 in the form of a yellowish-green solid/powder (1.5 mg). Characterization of isolate G1 using the FTIR spectrophotometer showed that there were vibrations of the alcohol O-H groups (3446.79 cm-1), aliphatic C-H (2958.80-2858.51 cm-1), C=C aromatic (1635.64 cm-1), C=C aromatic (1635.64 cm-1), C =O (1730.15 cm-1), C-O alcohol (1122.57 cm-1), and aliphatic C-H (1463.97-1382.96 cm-1). Based on a comparison of the spectra of isolate G1 with the spectra from the literature, isolate G1 was predicted as a flavonoid compound in the flavan or flavanol groups